The Growth, Production, and Quality of Shallot at Inland Quartz Sands (Quarzipsamments) in the off Season - Anang Firmansyah; Andy Bhermana (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
The development of shallot cultivation at back quartz sand during rainy or off season can be considered as new innovation. The objectives of this study is to obtain shallot varieties that are adaptive in terms of the growth, production, and quality parameters. The research was conducted during off season in Palangkaraya. The experimental design used in this research is randomized block design (RBD) 4x3 with 4 treatments of varieties (Maja Cipanas, Tajuk, Bauji and Bima Brebes), and 3 replication for each treatment. The results showed that soil bulk density increased with the deepening of the soil, however soil water content decreased. Based on growth parameter, Tajuk showed the best results and significantly different comparing to Bima Brebes, with plant height consecutively 46.88 cm and 39.52 cm, number of leaves 70.7 and 35.27 and number of shoot 13.43 and 6.60. For production parameter, the weight of varieties of Maja Cipanas, Bauji dan Bima Brebes is 10 grams more than Tajuk with weight is 6,97 grams only. The produstion of Tajuk is low and not significantly different from Bima Brebes, with production is respectively 15.28 ton/ha and 13.31 ton/ha, while the varieties of Bauji showed the highest dry production of 22.4 ton/ha although it is not significantly different with Maja Cipanas that can produce 18.49 ton/ha. For quality parameter, the varieties of Bima Brebes showed the optimum results in terms of parameter of hardness of tubers and total dissolved solids (TDS) with the value of 4.9 kg /cm2 and 16,42 % respectively.